PENINGKATAN KOMPETENSI GURU DALAM MENYUSUSN INDIKATOR PENGEMBANGAN KARAKTER BERBASIS AKM - Danang Prastyo; Fanny, Arif Mahya; Rarasaning Satianingsih; Apri Irianto; Ida Sulistyowati (Kanigara, 2022)
The competence of elementary school teachers in the preparation of AKM-based character development indicators needs to be a concern. Most of the teachers at SDN Sumur Welut III Surabaya, the teachers do not have experience in compiling AKM-based character development indicators. The purpose of this community service is to improve the competence of elementary school teachers in compiling AKM-based character development indicators. The intended target is the teacher of SDN Sumur Welut III Surabaya. This activity is carried out in the form of training and workshops, starting with material presentations, discussions, and workshops with the assistance of lecturers and assisted by students during group work. The results of the activity show that: (1) there is an increase in the understanding and skills of teachers in preparing AKM-based character development indicators; (2) The response of this training participant showed a positive response.